Prevalência de sarcopenia e seus fatores associados em pessoas vivendo com o vírus da imunodeficiência humana - Ximenez, Jaine Alves (2023)
People living with HIV/AIDS (PLWHA) are at increased risk of developing sarcopenia, making them more vulnerable to adverse clinical outcomes, such as poorer quality of life (QoL). The etiology is multifactorial and appears to be influenced by numerous factors. There is still no consensus on the ideal diagnostic criteria to identify sarcopenia in PLWHA, and no study has proposed specific cutoff points to determine low muscle strength and mass in this population, tested in relation to the QoL outcome. Current cutoff points may underestimate the true prevalence of sarcopenia and its association with adverse outcomes. Therefore, this study aims to: i) analyze the accuracy of handgrip strength (HGS) in identifying poorer QoL in PLWHA; ii) identify factors associated with sarcopenia and compare sarcopenia defined according to the EWGSOP2 algorithm using the cutoff points for low muscle strength recommended by the consensus with those identified in this study; iii) to evaluate the association between sarcopenia, constructed from different cutoff points for muscle strength, according to the EWGSOP2 algorithm, and QoL in PLWHA, in order to identify which criteria are best associated with worse QoL. To this end, two manuscripts were produced, both with a cross-sectional design and the same population, conducted between April 2023 and December 2024, with PLWHA using antiretrovirals, treated at a university hospital and a specialized care service in Dourados-MS. Patients ≥20 years old, of both sexes, with capacity to perform the assessments were included. Sociodemographic, clinical, lifestyle and anthropometric data were collected through interviews and medical records. Sarcopenia was defined based on the EWGSOP2 algorithm, with low muscle strength determined by HGS (kg) and low muscle mass by the appendicular skeletal muscle mass index (ASMI) (kg/m2) determined at the 20th percentile of the sample distribution, considering two constructs: (1) HGS <27 kg (men) and <16 kg (women) and ASMI <8.74 kg/m² (men) and <6.96 kg/m² (women); and (2) low muscle strength defined at the HGS cutoff points determined in the diagnostic accuracy analyses of this study and ASMI <8.74 kg/m² (men) and <6.96 kg/m² (women). The WHOQOL-HIV Bref instrument was used to assess perceived QoL. The cutoff points were determined using the diagnostic accuracy measures. The chi-square test was used to estimate associations in categorical variables. Odds ratio (OR) and 95% confidence interval (95%CI) were calculated to assess the magnitude of associations. A total of 105 PLWHA participated, with a mean age of 44.6 ± 13.5 years. As results of the first manuscript, the cutoff points with the best discriminatory power for worse QOL were ≤33/26 kg for HGS for men and women, respectively (construct 2). The prevalence of sarcopenia was higher in construct 2 (16.2%). Low CD4+ T lymphocyte count (≤200 cells/mm³) was associated with sarcopenia, regardless of the cutoff point adopted (<27/16 kg: OR = 4.09; 95% CI: 1.14–14.73; ≤3/26 kg: OR = 4.07; 95% CI: 1.29–12.88). Worse QoL was only associated with the construct using HGS ≤33/26 kg (OR = 5.12; 95% CI: 2.02–12.98). In the second manuscript, patients with sarcopenia had a 5.35-fold increase in the chance of reporting worse quality of life compared to non-sarcopenic patients (OR = 5.35; 95% CI: 2.11– 13.60). In conclusion, low muscle strength using the cutoff points ≤33 kg for men and ≤26 kg for women showed better diagnostic accuracy for worse QoL in PLWHA. Sarcopenia was associated with immunosuppression regardless of the cutoff point adopted for low muscle strength. HGS cutoff points ≤33/26 kg showed better applicability for early screening in outpatient settings, while the consensus cutoff point (<27/16 kg) seems more useful in scenarios of greater clinical severity. Patients with sarcopenia, according to EWGSOP2 and the cutoff points of this study, were more likely to report worse QOL. Our findings suggest the need to adopt higher cutoff points for PLWHA, enabling early diagnosis and interventions.